2014
DOI: 10.1260/2040-2317.5.3.189
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Creep Buckling Phenomenon of Steel Columns Subjected to Fire

Abstract: This paper presents highlights of on-going research, which aims at developing analytical, computational and experimental predictions of the phenomenon of creep buckling in steel columns subjected to fire. Analytical solutions using the concept of time-dependent tangent modulus are developed to model time-dependent buckling behavior of steel columns at elevated temperatures. Results from computational creep buckling studies using Abaqus are also presented, and compared with analytical predictions. Material cree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Most of the research regarding the influence of creep on the buckling response of columns has been published in the form of numerical studies combined with either explicit creep modelling [12,13] or a reduced tangent-modulus model [14]. The main conclusion from these studies was that creep influences the critical temperatures of columns beyond 400 • C, when they can be significantly reduced due to the inclusion of an explicit creep component.…”
Section: Previous Numerical and Test Studiesmentioning
confidence: 99%
“…Most of the research regarding the influence of creep on the buckling response of columns has been published in the form of numerical studies combined with either explicit creep modelling [12,13] or a reduced tangent-modulus model [14]. The main conclusion from these studies was that creep influences the critical temperatures of columns beyond 400 • C, when they can be significantly reduced due to the inclusion of an explicit creep component.…”
Section: Previous Numerical and Test Studiesmentioning
confidence: 99%
“…The Eurocode constitutive model implicitly accounts for the effect of high-temperature creep [8] and has been shown to facilitate a realistic resistance predictions for structural steel beams at elevated temperatures [4]. Morovat et al [9] explicitly investigated the effect of creep on the buckling behaviour and strength of steel columns at elevated temperatures by using different material creep models; the study concluded that different creep models can lead to rather different column buckling resistances and that there is a clear need for more extensive and reliable creep data for carbon steels. Based upon a large dataset of elevated temperature coupon test results collected from literature, Khorasani et al [10] found that the strength and stiffness reduction factors for hot-rolled carbon steel given in EN 1993-1-2 [5] are generally accurate, though slightly conservative, compared to those obtained from the tests.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese code requires that columns in high-rise buildings have a fire resistance rating of either 2.5 h or 3.0 h, depending on the type of the building [ 6 ]. To meet the requirements, steel columns in the prefabricated and modular construction must be protected [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, the fire protection must be optimized to fit the process of prefabrication in factory and modular assembly on-site.…”
Section: Introductionmentioning
confidence: 99%